ALTERASI DAN MINERALISASI SULFIDA PROSPEK X, TAMBANG EMAS MARTABE, BATANGTORU, TAPANULI SELATAN, SUMATERA UTARA - Canggara, Himerius
X prospect is located in Aek Pining Village, Batatoru Subdistrict, South Tapanuli Regency, North Sumatra, in the Contract of Work (CoW) area which belongs to PT. Agincourt Resources. The study was conducted on seventeen drill holes which are presented in three geological sections, namely OB1, OB2, and OB3. This research used petrographic analysis on both thin and polished section, Analytical Spectral Devices (ASD) and statistical data processing of geochemical assay. The study area consisted of two lithologic units, from oldest to youngest, hornblende andesite unit, and sandy matrix breccia unit. The hornblende andesite rock unit is pervasively altered by four types of alterations; they are vuggy - massive silica, alunite - dickite ± quartz, ilite - smectite ± kaolinite ± quartz, chlorite - calcite - ilite ± smectite ± quartz. Sandy matrix breccia are pervasively altered by three types of alterations; vuggy - massive silica, alunite - dickite ± quartz, and ilite - smectite ± kaolinite ± quartz. There are three types of sulphide minerals in the study area, sorted from oldest to youngest, are pyrite, enargite, and covellite. Sulfur Content in Sulphide (SCIS) valueswere used in this study to distinguish zones of intense oxidation (SCIS <3), and zones of low oxidation (sulfide zone) (SCIS> 3) in the study area. The coefficient of the Spearman’s Rank correlation on geochemical assay data in the sulfide zone shows good (r = 0,5-0,7) to excellent (r > 0,75) positive correlation between Cu, Au, Ag, As. Based on the results of the correlation, gold mineralization is interpreted to be associated with enargite mineralization.